Developmental Psychology of Learners: Environmental Factors Influencing Child Development. - Ahda Dana Ilahy; Muhammad Silmi Kaaffah; Eva Latipah; Ahmad Ali Ath Har; Dinda Bestari (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction to The Problem : Child development constitutes a progressive process influenced by both genetic and environmental factors. The environment plays a significant role in shaping the child’s physical, cognitive, social, and emotional domains. The family unit, peer groups, educational institutions, and cultural values are highly influential in determining the trajectory and overall quality of developmental outcomes. Purpose : This research aims to analyze the impact of environmental factors—specifically social elements, parenting styles, education, nutrition, and culture—on child development. This investigation is crucial for providing a comprehensive understanding, which will serve as the foundation for reinforcing effective educational and child-rearing strategies. Design/methods/approach : This study utilized a literature review method, involving the rigorous examination of current scientific literature, academic journals, and relevant educational psychology textbooks. The data were acquired through document analysis focusing on the impact of the environment on child development. Findings : Research indicates that a warm and responsive family environment promotes the child’s sense of security and self-confidence. Interactions with peers cultivate essential social skills and the development of self-identity. Quality education stimulates cognitive and social capacities, whereas adequate nutrition underpins physical growth and neurological development. Cultural values further shape the child’s character and behavioral patterns. Conversely, an adverse environment may impede the achievement of optimal development in the child. Research implications/limitations : This study is qualitative, thereby restricting its generalizability; nevertheless, it offers profound insight into the interaction of various environmental factors. Furthermore, the variation in cultural context constitutes an additional limitation regarding the universal applicability of the findings. Originality/value : This article presents an integrated analysis concerning the influence of the environment on child development and highlights the importance of collaboration among parents, educators, and the community in fostering a conducive environment. Further research is recommended for the development of culturally and socially based intervention models.